Pharmacists’ Role in Cardiovascular Disease Management in Saudi Arabia:A Systematic Review - Riyadh Atitallah Alghanmy,; Nawaf Attitallah Albeladi,; Sabri Abdullah Alraigi,; Abdulrahman Salem Alghamdi,; Faisal Ahmed Alamari,; Sultan Thawab Almutairi,; Wafaa Obaid Albushri,; Osama Mohammed Alsahafi,; Mohammed Atiahallah Alghanmi,; Ahmed Mohammed Saad Shuwaila, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: The purpose of this review is to assess the extent of the professional activities of pharmacists with regards to cardiovascular disease (CVD) in Saudi Arabia with regard to patient care and medication management and health-related outcomes. Methods: The current systematic review was performed according to the PRISMA statement. This was followed by a search in PubMed, Medline, and Google Scholar using the following search terms; cardiovascular disease, pharmacist intervention as well as Saudi Arabia. Results: The results help to determine that the practical activities involving pharmacists, medication management and adherence, counseling and lifestyle interventions positively affect clinical outcomes including blood pressure and cholesterol levels. That there are some barriers to involvement of pharmacist which are; regulatory and patent awareness barriers. Conclusion: New insight has been provided concerning the aspects of the role of pharmacists in management of CVD and the impact on patient’s clinical performance in Saudi Arabia. Improving such barriers can increase the impact of those recommendations even for the country’s healthcare agenda and for better population health by expanding integrated approaches to CVD management.